2013
DOI: 10.1021/jp407863s
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Small Magnetite Nanocrystals

Abstract: This paper focuses on the study of the magnetic properties of 9 nm magnetite nanocrystals. XRD and TEM measurements indicate the presence of crystalline particles, with a fraction of them only partially crystallized or highly defective. The analysis of the temperature dependence of the zero-field-cooled/field-cooled magnetization and of the thermoremanent magnetization provides evidence of the existence of three magnetic regimes: a high temperature regime (300-100 K), an intermediate regime (100-20 K), and a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 30 publications
12
44
0
Order By: Relevance
“…Magnetic nanoparticles (NPs) are complex physical objects that are interesting from both fundamental [1][2][3][4] and technological points of view (e.g., MRI, 5 hyperthermia, 6 drug delivery, 5,7 catalysis, 8 microwave applications 9 ). For magnetic monodomain particles with uniaxial anisotropy and easy axis alignment in the direction of the external field m 0 H, the energy can be written as:…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles (NPs) are complex physical objects that are interesting from both fundamental [1][2][3][4] and technological points of view (e.g., MRI, 5 hyperthermia, 6 drug delivery, 5,7 catalysis, 8 microwave applications 9 ). For magnetic monodomain particles with uniaxial anisotropy and easy axis alignment in the direction of the external field m 0 H, the energy can be written as:…”
Section: Introductionmentioning
confidence: 99%
“…With the decrease of particle size, charge ordering is known not as efficient and not as fast as in the bulk magnetite, which makes a smooth decrease of magnetic susceptibility around the transition. 39,40 Also noteworthy in M-T curve of Fe 3 O 4 NPs is the small broad mound centered at 35 K in ZFC measurement. In Fe 3 O 4 NPs with a sharp decrease of magnetization such as in our study, this broad mound is regularly observed.…”
Section: Resultsmentioning
confidence: 99%
“…In Fe 3 O 4 NPs with a sharp decrease of magnetization such as in our study, this broad mound is regularly observed. 40 One reason would be the glass-like transition with a sharp decrease of magnetization, which is caused by electrical low temperature tunnelling. 41 The other assumption is that there is a partial surface oxidation in Fe 3 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In many AFM/FM materials, this broad transition at low temperature is observed. 51,52 With the hysteresis shift in M exists. There is AFM-FM interaction between them, and this interaction causes magnetic transition at around 60 K (Figure 6b), which is clearly observed in the derivative curves ( Figure 7).…”
Section: Resultsmentioning
confidence: 99%